Lead paste of lead-acid storage battery for starting and lead-acid storage battery for starting

By using modified cerium oxide and carbon-coated strontium titanate, the problems of active material shedding and insufficient low-temperature discharge capacity in lead-acid batteries during cycle use have been solved, achieving long battery life and high-efficiency discharge performance.

CN121483987AActive Publication Date: 2026-02-06WUHAN CHANGGUANG BATTERY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202610032571.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-12
Publication Date
2026-02-06
Estimated Expiration
2046-01-12

AI Technical Summary

Technical Problem

Lead-acid batteries suffer from short lifespan and insufficient low-temperature, high-rate discharge capacity due to softening and shedding of the positive electrode active material and passivation of the negative electrode plate during cyclic use.

Method used

By using modified cerium oxide and carbon-coated strontium titanate, the internal resistance of the electrode is reduced by modifying cerium oxide, forming a mechanically stable framework to limit the excessive growth of PbSO4 crystals. The carbon-coated strontium titanate prevents the formation of PbSO4 layer. In2O3 is added to the negative electrode to suppress hydrogen evolution, thereby improving the battery stability and low-temperature discharge performance.

Benefits of technology

It significantly improves the cycle durability and ultra-low temperature high-rate discharge capability of lead-acid batteries, extends battery life, and enhances battery discharge performance in low-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The lead paste comprises a positive lead paste and a negative lead paste, the positive lead paste comprises modified cerium oxide, and the negative lead paste comprises carbon-coated strontium titanate and In2O3. The lead paste for the lead-acid storage battery for starting, provided by the invention, can be used for inhibiting active substances from falling off, remarkably improving the cycle durability of the lead-acid storage battery, delaying the passivation of a negative electrode and improving the ultra-low-temperature high-rate discharge capability of the lead-acid storage battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of lead-acid storage batteries, in particular to a lead paste for starting lead-acid storage batteries and a starting lead-acid storage battery. BACKGROUND

[0002] As a safe and reliable starting power supply, lead-acid storage batteries have two pain points in the use process for starting purposes. One is the cycle endurance capability, the number of cycle uses is insufficient, the battery service life is short, and the failure mode is that the positive active material softens and falls off to cause failure. The reason is that the PbO2 particles soften and fall off due to repeated expansion and contraction during the charge and discharge cycle. The other pain point is low-temperature high-rate discharge, the battery voltage drops quickly, the starting capability is insufficient, and the failure mode is that the negative plate generates a passivation layer in a low-temperature environment. The reason is that the solubility of PbSO4 drops sharply, the generation rate of PbSO4 is much higher than the dissolution rate, and the PbSO4 reaches supersaturation instantaneously, and the PbSO4 quickly crystallizes into a dense insulating layer (the thickness can reach 1-2 μm), which blocks the high-rate discharge from continuing. SUMMARY

[0003] Therefore, the present application provides a lead paste for starting lead-acid storage batteries and a starting lead-acid storage battery.

[0004] The technical scheme of the present application is as follows:

[0005] In a first aspect, the present application provides a lead paste for starting lead-acid storage batteries, comprising a positive lead paste and a negative lead paste, wherein the positive lead paste comprises modified cerium oxide, and the negative lead paste comprises carbon-coated strontium titanate and In2O3.

[0006] Further, the preparation method of the modified cerium oxide comprises the following steps: S1, dispersing cerium oxide in water to obtain a suspension;

[0007] S2, dissolving melamine in water to prepare a solution;

[0008] S3, under stirring, the solution is added dropwise into the suspension to obtain a mixture, and the stirring is continued, the solid is collected by centrifugation, and the precursor powder is obtained after drying;

[0009] S4, the precursor powder is placed in an inert gas atmosphere, heated, kept warm, and cooled to room temperature to obtain modified cerium oxide.

[0010] The prepared modified cerium oxide is nitrogen-doped graphene coated cerium oxide.

[0011] The flexible and high-strength nitrogen-doped graphene shell tightly coats and connects the cerium oxide and the surrounding active material particles to form a mechanically stable framework that can limit the excessive growth of PbSO4 crystals. During discharge, PbSO4 forms fine and uniform crystals rather than coarse and destructive crystals. The outer graphene absorbs and disperses stress through its elastic deformation during the volume change caused by the mutual transformation of PbO2 and PbSO4, preventing the loss of electrical contact between active material particles and the collapse of the microstructure. In addition, nitrogen doping can stabilize the carbon lattice of graphene, increase its electrochemical oxidation potential, slow down the process of oxidation to CO2, extend the service life of the conductive network, improve stability, inhibit hydrogen and oxygen evolution, and help reduce water electrolysis and grid corrosion.

[0012] Ce of the cerium oxide 3+ / Ce 4+ Variable valence and oxygen vacancies cause the positive electrode potential to rise at the end of charging, resulting in the evolution of oxygen. Cerium oxide can capture and temporarily lattice oxygen, mitigating the oxygen evolution process, reducing its overpotential, and reducing the corrosion of the grid.

[0013] By mitigating oxygen evolution, cerium oxide stabilizes the PbO2 lattice and protects the structural integrity of the active material.

[0014] On the basis of the above technical scheme, further, the mass ratio of the cerium oxide to melamine is 1: (2-5).

[0015] On the basis of the above technical scheme, further, the inert atmosphere is one or both of argon and nitrogen.

[0016] On the basis of the above technical scheme, further, the temperature in step S4 is raised to 600-800℃ at a rate of 5℃ / min, and the temperature is maintained at 600-800℃ for 2-3h.

[0017] On the basis of the above technical scheme, further, the preparation method of the carbon-coated strontium titanate comprises: A1, dispersing strontium titanate in a sucrose solution to obtain a mixed solution;

[0018] A2, reacting the mixed solution in a high-pressure reaction kettle, cooling, centrifuging, drying, and collecting the product;

[0019] A3. The product is placed in an inert atmosphere, heated, kept at that temperature, and cooled to room temperature to obtain the carbon-coated strontium titanate.

[0020] Negative electrode passivation is due to the formation of a dense, continuous, and insulating PbSO4 layer. Carbon-coated strontium titanate can prevent the formation of this PbSO4 layer. During low-temperature, high-rate discharge, carbon-coated strontium titanate undergoes rapid double-layer charging and discharging, instantly diverting some of the current. This directly reduces the instantaneous current density on the surface of the lead active material, thus preventing Pb from passing through. 2+ The dissolution rate of ions and the formation rate of PbSO4 are slowed down, thereby delaying the passivation of the negative electrode.

[0021] The uniformly dispersed carbon-coated strontium titanate particles provide numerous inert heterogeneous nucleation sites for PbSO4 precipitation. PbSO4 tends to nucleate at these sites, promoting the formation of fine, loose, and dispersed particle aggregates rather than a dense, continuous film. The loose structure allows for continued permeation of electrolyte and ions, sustaining the reaction.

[0022] The carbon coating itself is a conductor, and the dispersed carbon-coated strontium titanate particles can be connected into a network through carbon nanotubes. Electrons can be transported through the carbon network, which slows down the voltage drop.

[0023] The introduction of carbon-coated strontium titanate reduces the hydrogen evolution overpotential, exacerbating the hydrogen evolution reaction and leading to water loss and reduced charging efficiency. Adding In₂O₃ allows it to co-deposit on the lead surface, forming an alloy layer with a high hydrogen overpotential, effectively suppressing hydrogen production and ensuring that the lead-acid battery's water circulation and charging efficiency remain at a high level.

[0024] Based on the above technical solution, the mass ratio of strontium titanate to sucrose is further 1:(1~2).

[0025] Based on the above technical solution, the reaction is further carried out at 160~180℃ for 8~12 hours.

[0026] Based on the above technical solution, further, the temperature rise in step A3 is increased to 500~600℃ at a rate of 5℃ / min, and the heat preservation is maintained at 500~600℃ for 2~3 hours.

[0027] Based on the above technical solutions, the positive electrode lead paste further includes lead powder, red lead, dilute sulfuric acid, water, short fibers and polyvinylpyrrolidone.

[0028] Based on the above technical solution, further, by weight, the positive electrode lead paste includes 0.5-2 parts modified cerium oxide, 100-120 parts lead powder, 4.5-6 parts red lead, 10-12 parts dilute sulfuric acid, 12-15 parts water, 0.8-1 parts short fiber and 0.8-1 parts polyvinylpyrrolidone.

[0029] The role of polyvinylpyrrolidone is to improve the uniformity of lead paste and prevent the agglomeration of modified cerium oxide. It also acts as a binder, helping the active material adhere more firmly to the grid, increasing electrode strength, and promoting the formation of finer, more uniformly distributed PbSO4 crystals during discharge.

[0030] Short fibers are used in both positive and negative lead pastes. Their main function is to increase the mechanical strength of the active material, prevent the lead paste from falling off, and improve the cycle life of the battery.

[0031] Based on the above technical solutions, the negative electrode lead paste further includes lead powder, carbon nanotubes, dilute sulfuric acid, water, short fibers, sodium lignosulfonate, humic acid, and barium sulfate.

[0032] Based on the above technical solution, further, by weight, the negative electrode lead paste comprises 100-120 parts lead powder, 0.5-2.5 parts carbon-coated strontium titanate, 0.01-0.05 parts carbon nanotubes, 0.05-0.25 parts In2O3, 0.05-0.1 parts short fibers, 0.01-0.05 parts humic acid, 10-12 parts dilute sulfuric acid, 12-15 parts water, 0.01-0.05 parts sodium lignosulfonate, and 0.05-0.15 parts barium sulfate.

[0033] The role of carbon nanotubes in the negative electrode is to act as a conductor, reducing impedance during discharge and improving the utilization rate of active materials.

[0034] Sodium lignosulfonate adsorbs hydrophobic groups on the surface of lead particles in the negative electrode plate, generating a repulsive force towards the electrolyte, preventing lead deposition, avoiding the reduction of its surface area, and effectively improving the low-temperature high-rate discharge performance of the battery.

[0035] Humic acid, as an additive for the negative electrode active material, can be adsorbed onto the surface of lead crystals on the negative electrode plate. This allows lead to maintain its high dispersibility, and during discharge, the formed PbSO4 cannot directly surround the lead particles, preventing the negative electrode plate from shrinking. Therefore, humic acid has a significant effect on improving the discharge capacity of the battery, especially the low-temperature discharge capacity. Humic acid also increases the overpotential of hydrogen and reduces self-discharge. Among these effects, the carboxyl groups of humic acid play an important role in the depolarization of lead-acid batteries.

[0036] The role of barium sulfate is to provide nuclei for PbSO4 deposition during battery discharge. Adding inert barium sulfate provides a large surface area for PbSO4 deposition, preventing the formation of a water-impermeable passivation layer and thus preventing electrode passivation. BaSO4 also improves the high-rate performance of the battery at low temperatures.

[0037] Based on the above technical solutions, the short fiber is further defined as either polypropylene fiber or aramid fiber.

[0038] Based on the above technical solutions, the fineness of the short fibers is further improved to 0.35-0.5D.

[0039] Secondly, the present invention also provides a lead-acid battery for starting.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The lead paste for starting lead-acid batteries provided by this invention can inhibit the shedding of active materials, significantly improve the cycle durability of lead-acid batteries, delay negative electrode passivation, and improve the high-rate discharge capability of lead-acid batteries at ultra-low temperatures. Detailed Implementation

[0042] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0043] In the following specific implementation, polyvinylpyrrolidone was purchased from Beyotime Biotechnology Co., Ltd., with product number Y175957-100g.

[0044] In the following specific embodiments, the density of dilute sulfuric acid is 1.4 g / cm³. 3 .

[0045] Example 1 This embodiment provides a starting lead-acid battery paste, including positive lead paste and negative lead paste.

[0046] The positive electrode lead paste comprises the following components in parts by weight: 1.5 parts modified cerium oxide, 110 parts lead powder, 5 parts red lead, 11 parts dilute sulfuric acid, 14 parts deionized water, 0.9 parts polypropylene fiber, and 0.9 parts polyvinylpyrrolidone, with 1 part by weight being 1 kg.

[0047] The preparation method of modified cerium oxide includes the following steps: S1, dispersing 10g of cerium oxide in 500mL of water to obtain a suspension;

[0048] S2. Dissolve 30g of melamine in 600mL of water to prepare a solution;

[0049] S3. Under stirring, the solution is slowly added dropwise to the suspension to obtain a mixture. The mixture is stirred continuously, centrifuged at 1000 rpm for 10 min to collect the solid, and dried to obtain the precursor powder.

[0050] S4. The precursor powder is placed in an Ar atmosphere and heated to 700°C at a rate of 5°C / min, held at that temperature for 3 hours, and then cooled to room temperature to obtain modified cerium oxide.

[0051] The preparation method of the positive electrode lead paste is as follows: A1. Add lead powder and red lead to a paste mixer and mix well;

[0052] A2. Add deionized water and mix well;

[0053] A3. Add dilute sulfuric acid to adjust the negative pressure of the paste mixer to 180 mbar and the temperature to 60℃;

[0054] A4. Add polypropylene fiber, polyvinylpyrrolidone, and modified cerium oxide, mix evenly, cool to room temperature, and dispense the paste to obtain positive electrode lead paste.

[0055] The negative electrode lead paste comprises the following components in parts by weight: 110 parts lead powder, 1 part carbon-coated strontium titanate, 0.02 parts carbon nanotubes, 0.1 parts In2O3, 0.08 parts short fibers, 0.03 parts humic acid, 11 parts dilute sulfuric acid, 14 parts deionized water, 0.04 parts sodium lignosulfonate, and 0.1 parts barium sulfate, where 1 part by weight is 1 kg.

[0056] The method for preparing carbon-coated strontium titanate includes the following steps: wherein the sucrose solution is obtained by dissolving 15g of sucrose in 100mL of water.

[0057] C1. Disperse 10g of strontium titanate in a sucrose solution to obtain a mixed solution;

[0058] C2. The mixed solution was reacted in a high-pressure reactor at 170°C for 10 h. After cooling to room temperature, it was centrifuged at 1000 rpm for 10 min, dried, and the product was collected.

[0059] C3. The product is placed in an Ar atmosphere and heated to 550°C at a rate of 5°C / min, held at that temperature for 3 hours, and then cooled to room temperature to obtain the carbon-coated strontium titanate.

[0060] The preparation method of the negative electrode lead paste is as follows: B1. Add lead powder to the paste mixer and mix well;

[0061] B2. Add deionized water and mix well.

[0062] B3. Add dilute sulfuric acid and adjust the negative pressure of the paste mixer to 180 mbar and the temperature to 60℃.

[0063] B4. Add aramid fiber, carbon-coated strontium titanate, carbon nanotubes, humic acid, sodium lignosulfonate, barium sulfate, and In2O3, mix well, cool to room temperature, and dispense the paste to obtain positive electrode lead paste.

[0064] Example 2 This embodiment provides a starting lead-acid battery paste, including positive lead paste and negative lead paste.

[0065] The positive electrode lead paste comprises the following components in parts by weight: 0.5 parts modified cerium oxide, 100 parts lead powder, 4.5 parts red lead, 10 parts dilute sulfuric acid, 12 parts deionized water, 0.8 parts polypropylene fiber, and 0.8 parts polyvinylpyrrolidone, with 1 part by weight being 1 kg.

[0066] The preparation method of modified cerium oxide includes the following steps: S1, dispersing 10g of cerium oxide in 500mL of water to obtain a suspension;

[0067] S2. Dissolve 20g of melamine in 600mL of water to prepare a solution;

[0068] S3. Under stirring, the solution is slowly added dropwise to the suspension to obtain a mixture. The mixture is stirred continuously, centrifuged at 1000 rpm for 10 min to collect the solid, and dried to obtain the precursor powder.

[0069] S4. The precursor powder is placed in an Ar atmosphere and heated to 600°C at a rate of 5°C / min, held at that temperature for 2 hours, and then cooled to room temperature to obtain modified cerium oxide.

[0070] The preparation method of the positive electrode lead paste includes the following steps: A1. Add lead powder and red lead to a paste mixer and mix well;

[0071] A2. Add deionized water and mix well;

[0072] A3. Add dilute sulfuric acid to adjust the negative pressure of the paste mixer to 180 mbar and the temperature to 60℃;

[0073] A4. Add polypropylene fiber, polyvinylpyrrolidone, and modified cerium oxide, mix evenly, cool to room temperature, and dispense the paste to obtain positive electrode lead paste.

[0074] The negative electrode lead paste comprises the following components in parts by weight: 100 parts lead powder, 0.5 parts carbon-coated strontium titanate, 0.01 parts carbon nanotubes, 0.05 parts In2O3, 0.05 parts short fibers, 0.01 parts humic acid, 10 parts dilute sulfuric acid, 12 parts deionized water, 0.01 parts sodium lignosulfonate, and 0.05 parts barium sulfate, with 1 part by weight being 10 kg.

[0075] The method for preparing carbon-coated strontium titanate includes the following steps: wherein the sucrose solution is obtained by dissolving 20g of sucrose in 100mL of water.

[0076] C1. Disperse 10g of strontium titanate in a sucrose solution to obtain a mixed solution;

[0077] C2. The mixed solution was reacted in a high-pressure reactor at 160°C for 8 hours. After cooling to room temperature, it was centrifuged at 1000 rpm for 10 minutes, dried, and the product was collected.

[0078] C3. The product is placed in an Ar atmosphere and heated to 500°C at a rate of 5°C / min, held at that temperature for 2 hours, and then cooled to room temperature to obtain the carbon-coated strontium titanate.

[0079] The preparation method of the negative electrode lead paste is as follows: B1. Add lead powder to the paste mixer and mix well;

[0080] B2. Add deionized water and mix well.

[0081] B3. Add dilute sulfuric acid and adjust the negative pressure of the paste mixer to 180 mbar and the temperature to 60℃.

[0082] B4. Add aramid fiber, carbon-coated strontium titanate, carbon nanotubes, humic acid, sodium lignosulfonate, barium sulfate, and In2O3, mix well, cool to room temperature, and dispense the paste to obtain positive electrode lead paste.

[0083] Example 3 This embodiment provides a starting lead-acid battery paste, including positive lead paste and negative lead paste.

[0084] The positive electrode lead paste comprises the following components in parts by weight: 2 parts modified cerium oxide, 120 parts lead powder, 6 parts red lead, 12 parts dilute sulfuric acid, 15 parts deionized water, 1 part polypropylene fiber, and 1 part polyvinylpyrrolidone, with 1 part by weight being 1 kg.

[0085] The preparation method of modified cerium oxide includes the following steps: S1, dispersing 10g of cerium oxide in 500mL of water to obtain a suspension;

[0086] S2. Dissolve 50g of melamine in 600mL of water to prepare a solution;

[0087] S3. Under stirring, the solution is slowly added dropwise to the suspension to obtain a mixture. The mixture is stirred continuously, centrifuged at 1000 rpm for 10 min to collect the solid, and dried to obtain the precursor powder.

[0088] S4. The precursor powder is placed in an Ar atmosphere and heated to 800°C at a rate of 5°C / min, held at that temperature for 2.5 hours, and then cooled to room temperature to obtain modified cerium oxide.

[0089] The preparation method of the positive electrode lead paste is as follows: A1. Add lead powder and red lead to a paste mixer and mix well;

[0090] A2. Add deionized water and mix well;

[0091] A3. Add dilute sulfuric acid to adjust the negative pressure of the paste mixer to 180 mbar and the temperature to 60℃;

[0092] A4. Add polypropylene fiber, polyvinylpyrrolidone, and modified cerium oxide, mix evenly, cool to room temperature, and dispense the paste to obtain positive electrode lead paste.

[0093] The negative electrode lead paste comprises the following components in parts by weight: 120 parts lead powder, 2.5 parts carbon-coated strontium titanate, 0.05 parts carbon nanotubes, 0.25 parts In2O3, 0.1 parts short fibers, 0.05 parts humic acid, 12 parts dilute sulfuric acid, 15 parts deionized water, 0.05 parts sodium lignosulfonate, and 0.15 parts barium sulfate, where 1 part by weight is 1 kg.

[0094] The method for preparing carbon-coated strontium titanate includes the following steps: wherein the sucrose solution is obtained by dissolving 10g of sucrose in 100mL of water.

[0095] C1. Disperse 10g of strontium titanate in a sucrose solution to obtain a mixed solution;

[0096] C2. The mixed solution was reacted in a high-pressure reactor at 180°C for 12 hours. After cooling to room temperature, it was centrifuged at 1000 rpm for 10 minutes, dried, and the product was collected.

[0097] C3. The product is placed in an Ar inert atmosphere and heated to 600°C at a rate of 5°C / min, held at that temperature for 2.5 hours, and then cooled to room temperature to obtain the carbon-coated strontium titanate.

[0098] The preparation method of the negative electrode lead paste is as follows: B1. Add lead powder to the paste mixer and mix well;

[0099] B2. Add deionized water and mix well;

[0100] B3. Add dilute sulfuric acid and adjust the negative pressure of the paste mixer to 180 mbar and the temperature to 60℃.

[0101] B4. Add aramid fiber, carbon-coated strontium titanate, carbon nanotubes, humic acid, sodium lignosulfonate, barium sulfate, and In2O3, mix well, cool to room temperature, and dispense the paste to obtain positive electrode lead paste.

[0102] Example 4 This embodiment provides a starting lead-acid battery, which includes uniformly coating the positive electrode lead paste and negative electrode lead paste prepared in Example 1 onto the grid as the positive electrode plate and negative electrode plate, respectively.

[0103] Comparative Example 1 The difference between this comparative example and Example 1 is that the positive electrode lead paste does not contain modified cerium oxide.

[0104] Comparative Example 2 The difference between this comparative example and Example 1 is that the negative electrode lead paste does not contain carbon-coated strontium titanate.

[0105] Comparative Example 3 The difference between this comparative example and Example 1 is that the negative electrode lead paste does not contain In2O3.

[0106] Comparative Example 4 The difference between this comparative example and Example 1 is that the modified cerium oxide is in the amount of 5 parts by weight.

[0107] Comparative Example 5 The difference between this comparative example and Example 1 is that the weight of carbon-coated strontium titanate is 5 parts.

[0108] Comparative Example 6 The difference between this comparative example and Example 1 is that the weight of In2O3 is 5 parts.

[0109] Performance testing 1. The positive and negative lead pastes prepared in Examples 1-3 and Comparative Examples 1-6 were uniformly coated onto the lead-calcium alloy positive and negative electrode grids, respectively, using a coating density of 1.25 g / cm³. 3 Sulfuric acid was used as the electrolyte to prepare a starting lead-acid battery. A 40% DOD cycle durability test was conducted according to the test methods and standard requirements of GJB 1724A-2009. The test results are shown in Table 1.

[0110] Table 1. Cycle Durability Number of Examples and Comparative Examples

[0111] 2. The positive and negative lead pastes prepared in Examples 1-3 and Comparative Examples 1-6 were uniformly coated onto the lead-calcium alloy positive and negative electrode grids, respectively, using a coating density of 1.25 g / cm³. 3Using sulfuric acid as the electrolyte, a starting lead-acid battery with a rated voltage of 24V (12 cells in series) and a rated capacity of 130Ah was prepared. A high-rate discharge capability test at ultra-low temperature (-40℃) was conducted. The testing methods and standards are shown below, and the test results are shown in Table 2.

[0112] Test method: Place the fully charged battery in a -40℃ low temperature chamber for 24 hours, and then discharge it with a constant current of 390A for 75 seconds.

[0113] The standard requires that the voltage be no less than 14.4V after 30 seconds of discharge and no less than 12.0V after 75 seconds of discharge.

[0114] Table 2. Test results of ultra-low temperature high-rate discharge capability of the examples and comparative examples.

[0115] As shown in Tables 1 and 2, the lead-acid batteries prepared using the positive and negative electrode pastes of this invention have a high cycle durability and long cycle life. They also exhibit superior performance in ultra-low temperature high-rate discharge.

[0116] As can be seen from the comparison of Example 1 and the comparative example, when modified cerium oxide, carbon-coated strontium titanate, and In2O3 are not present, the cycle life and ultra-low temperature high-rate discharge performance of lead-acid batteries are significantly reduced.

[0117] When excessive amounts of modified cerium oxide, carbon-coated strontium titanate, and In₂O₃ are used, the cycle life and ultra-low temperature high-rate discharge performance of lead-acid batteries all decrease significantly. This is because excessive use of carbon-coated strontium titanate reduces the amount of active lead material per unit volume, leading to a decrease in the battery's initial capacity, potentially increased internal resistance, and altered pore structure of the lead paste. Excessive use of In₂O₃ increases side reactions, exacerbates self-discharge, and alters the structure of the active material. Excessive use of modified cerium oxide leads to a decrease in initial capacity and energy density, increased battery internal resistance, damage to electrode microstructure, and exacerbation of side reactions.

[0118] In summary, lead-acid batteries using the positive electrode paste of this invention as raw material are less prone to detachment and failure during cyclic charging and discharging, significantly improving their cycle life. Lead-acid batteries using the negative electrode paste of this invention as raw material are less prone to passivation of the negative electrode plate during ultra-low temperature, high-rate discharge, leading to starting failure. The battery discharge voltage platform is high, stable, and reliable, solving the problem of batteries struggling to release energy in low-temperature environments.

[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A starting lead-acid battery paste, characterized in that, It includes positive electrode lead paste and negative electrode lead paste, wherein the positive electrode lead paste includes modified cerium oxide, and the negative electrode lead paste includes carbon-coated strontium titanate and In2O3.

2. The lead paste for starting lead-acid batteries as described in claim 1, characterized in that, The method for preparing the modified cerium oxide includes: S1, dispersing cerium oxide in water to obtain a suspension; S2. Dissolve melamine in water to prepare a solution; S3. Under stirring, the solution is added dropwise to the suspension to obtain a mixture. The mixture is stirred continuously, the solid is collected by centrifugation, and after drying, the precursor powder is obtained. S4. The precursor powder is placed in an inert gas atmosphere, heated, kept at that temperature, and cooled to room temperature to obtain modified cerium oxide.

3. The lead paste for starting lead-acid batteries as described in claim 1, characterized in that, The method for preparing carbon-coated strontium titanate includes: A1, dispersing strontium titanate in a sucrose solution to obtain a mixed solution; A2. React the mixture in a high-pressure reactor, cool it, centrifuge, dry it, and collect the product. A3. The product is placed in an inert atmosphere, heated, kept at that temperature, and cooled to room temperature to obtain the carbon-coated strontium titanate.

4. The lead paste for starting lead-acid batteries as described in claim 1, characterized in that, The positive electrode lead paste also includes lead powder, red lead, dilute sulfuric acid, water, short fibers, and polyvinylpyrrolidone.

5. The lead paste for starting lead-acid batteries as described in claim 4, characterized in that, By weight, the positive electrode lead paste comprises 0.5-2 parts modified cerium oxide, 100-120 parts lead powder, 4.5-6 parts red lead, 10-12 parts dilute sulfuric acid, 12-15 parts water, 0.8-1 parts short fiber and 0.8-1 parts polyvinylpyrrolidone.

6. The lead paste for starting lead-acid batteries as described in claim 1, characterized in that, The negative electrode lead paste also includes lead powder, dilute sulfuric acid, water, short fibers, sodium lignosulfonate, humic acid, and barium sulfate.

7. The lead paste for starting lead-acid batteries as described in claim 6, characterized in that, By weight, the negative electrode lead paste comprises 100-120 parts lead powder, 0.5-2.5 parts carbon-coated strontium titanate, 0.01-0.05 parts carbon nanotubes, 0.05-0.25 parts In2O3, 0.05-0.1 parts short fibers, 0.01-0.05 parts humic acid, 10-12 parts dilute sulfuric acid, 12-15 parts water, 0.01-0.05 parts sodium lignosulfonate, and 0.05-0.15 parts barium sulfate.

8. A starting lead-acid battery, characterized in that, The lead paste for the starting lead-acid battery is the lead paste for the starting lead-acid battery as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Super lead storage battery anode active substance for electric automobile

    CN101964421A

  • Active material of super lead storage battery plate

    CN102024946A

  • Lead plaster of lead-acid storage battery and lead-acid storage battery

    CN112510182A

  • Deep-cycle long-life lead-acid storage battery lead paste for parking, battery thereof and manufacturing process method of battery

    CN113675397A

  • High-performance lead-carbon battery negative electrode lead paste formula and preparation method thereof

    CN113764627A